Phage Ligands for Identification of Mesenchymal-Like Breast Cancer Cells and Cancer-Associated Fibroblasts - Jones, Kelvin M.; Karanam, Balasubramanyam; Jones-Triche, Jacqueline; Sandey, Maninder; Henderson, Henry J.; Samant, Rajeev S.; Temesgen, Samuel; Yates, Clayton; Bedi, Deepa (Frontiers in Oncology, 2018)
Epithelial to mesenchymal transition (EMT) is believed to be crucial for primary tumors to escape their original residence and invade and metastasize. To properly define EMT, there is a need for ligands that can identify this phenomenon in tumor tissue and invivo. A phage-display selection screening was performed to select novel binding phage peptides for identification of EMT in breast cancer. Epithelial breast cancer cell line, MCF-7 was transformed to mesenchymal phenotype by TGF-β treatment and was used for selection. Breast fibroblasts were used for subtractive depletion and breast cancer metastatic cell lines MDA-MB-231, T47D-shNMI were used for specificity assay. The binding peptides were identified, and their binding capacities were confirmed by phage capture assay, phage-based ELISA, immunofluorescence microscopy. The phage peptide bearing the 7-amino acid sequence, LGLRGSL, demonstrated selective binding to EMT phenotypic cells (MCF-7/TGF-β and MDA-MB-231) as compared to epithelial subtype, MCF-7, T47D and breast fibroblasts (Hs578T). The selected phage was also able to identify metastatic breast cancer tumor in breast cancer tissue microarray (TMA). These studies suggest that the selected phage peptide LGLRGSL identified by phage-display library, showed significant ability to bind to mesenchymal-like breast cancer cells/ tissues and can serve as a novel probe/ligand for metastatic breast cancer diagnostic and imaging.